2010
DOI: 10.1099/mic.0.031146-0
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes does not survive ingestion by Acanthamoeba polyphaga

Abstract: Listeria monocytogenes is a ubiquitous bacterium capable of infecting humans, particularly pregnant women and immunocompromised individuals. Although the intracellular invasion and pathogenesis of listeriosis in mammalian tissues has been well studied, little is known about the ecology of L. monocytogenes, and in particular the environmental reservoir for this bacterium has not been identified. This study used short-term co-culture at 15, 22 and 37 6C to examine the interaction of L. monocytogenes strains with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…polyphaga . Moreover, Akya and colleagues [39] demonstrated the death of L . monocytogenes cells phagocytosed by A .…”
Section: Discussionmentioning
confidence: 99%
“…polyphaga . Moreover, Akya and colleagues [39] demonstrated the death of L . monocytogenes cells phagocytosed by A .…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies [83] demonstrated some functionality of different L. seeligeri virulence factors and our data suggest that the homologue of internalin A in the hemolytic L. innocua strain supports the ability to invade human intestinal epithelial cells (even though future experiments with an isogenic inlA mutant will be required to confirm this). One hypothesis is that the virulence genes in Listeria play a role in the survival of and defense against predation by protists, however this hypothesis is not supported by a recent study that demonstrates that L. monocytogenes does not survive ingestion by the amoeba Acanthamoeba polyphaga [84]. …”
Section: Discussionmentioning
confidence: 99%
“…These are indirect indications that protozoans can act as vectors of dispersion of L. monocytogenes in soil. However, other reports suggest that the ability of L. monocytogenes to survive after ingestion by protozoans may be strain and/or species specific as killing of L. monocytogenes by Acanthamoeba polyphaga , Acanthamoeba castellanii and Acanthamoeba lenticulata has been reported (Akya et al, 2009, 2010). …”
Section: Introductionmentioning
confidence: 99%